Beneficial effects of estrogen in a mouse model of cerebrovascular insufficiency. - Naohito Kitamura (Public Library of Science (PLoS), 2009)
Background The M(5) muscarinic acetylcholine receptor is known to play a crucial role in mediating acetylcholine dependent dilation of cerebral blood vessels. Previously, we reported that male M(5) muscarinic acetylcholine knockout mice (M5R(-/-) mice) suffer from a constitutive constriction of cerebral arteries, reduced cerebral blood flow, dendritic atrophy, and short-term memory loss, without necrosis and/or inflammation in the brain. Methodology/principal findings We employed the Magnetic Resonance Angiography to study the area of the basilar artery in male and female M5R(-/-) mice. Here we show that female M5R(-/-) mice did not show the reduction in vascular area observed in male M5R(-/-) mice. However, ovariectomized female M5R(-/-) mice displayed phenotypic changes similar to male M5R(-/-) mice, strongly suggesting that estrogen plays a key role in the observed gender differences. We found that 17beta-estradiol (E2) induced nitric oxide release and ERK activation in a conditional immortalized mouse brain cerebrovascular endothelial cell line. Agonists of ERalpha, ERbeta, and GPR30 promoted ERK activation in this cell line. Moreover, in vivo magnetic resonance imaging studies showed that the cross section of the basilar artery was restored to normal in male M5R(-/-) mice treated with E2. Treatment with E2 also improved the performance of male M5R(-/-) mice in a cognitive test and reduced the atrophy of neural dendrites in the cerebral cortex and hippocampus. M5R(-/-) mice also showed astrocyte swelling in cortex and hippocampus using the three-dimensional reconstruction of electron microscope images. This phenotype was reversed by E2 treatment, similar to the observed deficits in dendrite morphology and the number of synapses. Conclusions/significance Our findings indicate that M5R(-/-) mice represent an excellent novel model system to study the beneficial effects of estrogen on cerebrovascular function and cognition. E2 may offer new therapeutic perspectives for the treatment of cerebrovascular insufficiency related memory dysfunction.